Outward Currents Contributing to Inspiratory Burst Termination in preBötzinger Complex Neurons of Neonatal Mice Studied in Vitro - Krey, Rebecca A.; Goodreau, Adam M.; Arnold, Thomas B.; Del Negro, Christopher A. (Frontiers in Neural Circuits, 2010)
We studied preBötzinger Complex (preBötC) inspiratory interneurons to determine the cellular mechanisms that influence burst termination in a mammalian central pattern generator. Neonatal mouse slice preparations that retain preBötC neurons generate respiratory motor rhythms in vitro. Inspiratory-related bursts rely on inward currents that flux Na+, thus outward currents coupled to Na+ accumulation are logical candidates for assisting in, or causing, burst termination. We examined Na+/K+ ATPase electrogenic pump current (Ipump), Na+-dependent K+ current (IK–Na), and ATP-dependent K+ current (IK–ATP). The pharmacological blockade of Ipump, IK–Na, or IK–ATP caused pathological depolarization akin to a burst that cannot terminate, which impeded respiratory rhythm generation and reversibly stopped motor output. By simulating inspiratory bursts with current-step commands in synaptically isolated preBötC neurons, we determined that each current generates approximately 3–8 mV of transient post-burst hyperpolarization that decays in 50–1600 ms. Ipump, IK–Na, and – to a lesser extent – IK–ATP contribute to terminating inspiratory bursts in the context of respiratory rhythm generation by responding to activity dependent cues such as Na+ accumulation.